Activation of Mitochondrial Uncoupling Protein 4 and ATP-Sensitive Potassium Channel Cumulatively Decreases Superoxide Production in Insect Mitochondria - SlociŦ#132;ska, Malgorzata; Rosinski, Grzegorz; Jarmuszkiewicz, Wieslawa (Protein and Peptide Letters, 2016)
It has been evidenced that mitochondrial uncoupling protein 4 (UCP4) and ATP-regulated potassium channel (mKATP channel) of insect Gromphadorhina coqereliana mitochondria decrease superoxide anion production. We elucidated whether the two energy-dissipating systems work together on a modulation of superoxide level in cockroach mitochondria. Our data show that the simultaneous activation of UCP4 by palmitic acid and mKATP channel by pinacidil revealed a cumulative effect on weakening mitochondrial superoxide formation. The inhibition of UCP4 by GTP (and/or ATP) and mKATP channel by ATP elevated superoxide production. These results suggest a functional cooperation of both energy-dissipating systems in protection against oxidative stress in insects.
Keywords: superoxide production